ARTIFICIAL SUBCONSCIOUS - STRUNA, VADIM (Чернівці: Черн. нац. ун-т, 2022)
Here, in this work are presented a new part in computers world. And exactly, a new expression: Artificial Subconscious (ASU). Abbreviation sounds funny, but at the same time very memorable. Nowadays we could see how high speed has general development. Aim is to help humanity to receive artificial brain with more high precision and create a new technology in IT to do this. Figures from this paper will show us how we could obtain more dynamic calculus to receive a more efficiently decisions in computer systems in our days. In Artificial Intelligence must be more smart cells, which we could use in different situations of our needs. Besides of Artificial Intelligence in our days here will appear a new part of Computers and exactly: Artificial Subconscious, that always will be near the Artificial Intelligence. Also here will be too a part of technology – Knowledge base. This is three support pylon of our idea. This new smart cells will appear when is be necessary and will works with knowledge base. These cells will be as objects, classes in dynamic programming languages. This system also is based on these sleeping cells, which could help us in more difficult calculus, thereby we could have o very high level artificial brain. With this brain we must help humanity to find answer of many questions that could be apllyed to obtain new technology of our future and helped peoples to make right decisions, to save this planet from themselves.
Keywords: Conscious, Subconscious, Artificial Intelligence, Knowledge Base, Database, DNA, Cells, Python 3, OOP, Object, Cluster, Membrane Computing, Dynamic Language, Cell Programming, Artificial Subconscious, Decision.